Students' acceptance and motivation on andragogical approaches towards their academic performance / Nur Fairuz Wahida Ibrahim, Norizul Azida Darus and Amizura Hanadi Mohd Radzi - Ibrahim, Nur Fairuz Wahida; Darus, Norizul Azida; Mohd Radzi, Amizura Hanadi (Universiti Teknologi MARA, Perlis, 2022)
Online Distance Learning (ODL) has been practiced widely around the world. The educational delivery of ODL provides learners vast opportunities to deal with the learning process, that includes time, place as well as pace of learning. Assisted by technology, ODL has tremendously improved the educational system in many ways. This erupts the possibility of implementing andragogical approach through ODL. Hence, this study, which is guided by Knowles's theory of andragogy, is qualitative research investigating the issue of learning process via andragogical approaches of seven adult learners in UiTM Perlis, Malaysia. The study also seeks whether students' attitudes vary differently among themselves throughout ODL so that their performance during class could be evaluated. The findings of the study support andragogical approaches which they positively affect the students' learning experiences.